Dielectric and piezoelectric properties of PZT type ceramics obtained by the sol-gel method - Dukat, Monika; Zarycka, Aldona (Archives of Acoustics, 2007)
A sol-gel method belongs to chemical methods of producing non-organic and nonmetallic materials. As a result of a synthesis by the sol-gel method a powder with the Pb(Zr_0.35Ti_0.65)O_3 chemical composition, which was formed and sintered freely, and hot pressed as well, was obtained. The obtained ceramic material was subjected to test of properties of permittivity, loss tangent and piezoelectric properties as well. Both a description of a technological process to obtain ceramic materials by the sol-gel method and the determined dielectric and piezoelectric parameters of the ceramic in question are presented in this work. The ceramic in question can be used, among others, in pressure sensors, electroacoustic transducers, piezoceramic amplifiers, loudspeakers and microphones.